(untitled) (Research, Society and Development, 2020)
Ginger is a plant whose rhizome has a high therapeutic potential in combating various diseases due to the action of several of its constituents. The 6-gingerol, phenolic compounds and carotenoids, act on macrophage modulation, antiplatelet aggregation and immunosuppressive activity. This work aimed to determine the total antioxidant capacity as well as to evaluate the use of paper spray mass spectrometry to obtain fingerprints of ginger samples of conventional and organic cultivation. The results demonstrated that organic farming samples showed higher levels of fiber and total protein, as well as 6-gingerol. One must still give preference to organic Ginger intake since it presented significant levels of 6-gingerol, fiber and protein. Several chemical classes such as sugars, fatty acids, phenylpropanoids and flavonoids were identified in organic and conventional ginger through paper spray ionization mass spectrometry. This analysis proved to be a very efficient and fast technique for obtaining fingerprints of ginger, allowing the identification of 19 compounds in the positive mode and 28 in the negative mode.